LANGUAGE FEATURES OF TEACHER’S TALK IN TEACHING PROCEDURE TEXT FOR THE TWELFTH GRADE OF SENIOR HIGH SCHOOL AT SMA SWASTA TUNAS PELITA BINJAI - Siska Rahayu; Amrin Saragih; Isli Iriani Indiah Pane (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2017)
This study aims at analyzing features of teacher’s talk in teaching procedure text. The data of the study were the script of utterances the teacher and students. The source of data were the twelfth grade of Senior High School at SMA Swasta Tunas Pelita Binjai where the teacher taught 27 students in one class. This study was used descriptive qualitative. SETT (Self Evaluation of Teacher Talk) framework used to identify and classified features of teacher talk during learning process which used video recording and field notes. The finding of the study showed that the dominant feature of teacher talk was extended leaner-turn (41, 6%). This feature effected on the students’ learning process because the teacher gave the opportunity to the learners to deliver their ideas, it could improve the learners’ speaking skill. Keywords :  Procedure Text, Features of Teacher Talk, Learning Process.